2017
DOI: 10.1016/j.jcot.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic locked plating for fixation of distal femur fractures using near- cortical over-drilling: Preliminary results of a prospective observational study

Abstract: Dynamic locked plating using near-cortex over-drilling is a simple technique that uses standard locked plates that promotes callus formation when used for fixing distal femur fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Besides, the overdrilling of the near cortex allows an axial toggling of the screw shaft in the near cortex bone hole, which enhances a more elastic plate fixation with rather parallel axial movements of the bone fragments and reduced shear motions at the fracture site. This was not investigated in the current study, however, previous work reported that overdrilling of the near cortex fostered callus formation and bone healing in a first case series of distal femur fractures . Therefore, those expected benefits of the LagLoc fixation, together with its potentially better overall stability, can justify the use of an additional instrument and one locking screw instead of a cheaper lag screw, compared to the locking plate technique with the use of a compression screw through a plate hole.…”
Section: Discussionmentioning
confidence: 85%
“…Besides, the overdrilling of the near cortex allows an axial toggling of the screw shaft in the near cortex bone hole, which enhances a more elastic plate fixation with rather parallel axial movements of the bone fragments and reduced shear motions at the fracture site. This was not investigated in the current study, however, previous work reported that overdrilling of the near cortex fostered callus formation and bone healing in a first case series of distal femur fractures . Therefore, those expected benefits of the LagLoc fixation, together with its potentially better overall stability, can justify the use of an additional instrument and one locking screw instead of a cheaper lag screw, compared to the locking plate technique with the use of a compression screw through a plate hole.…”
Section: Discussionmentioning
confidence: 85%
“…No other complications were reported. Galal (2017). In Ziran et al study of thirtyive patients, there was also a male preponderance seen and the meantime to fracture union was 16 weeks.…”
Section: Resultsmentioning
confidence: 94%
“…Near-cortical over-drilling allows for some motion between the screw and the near-cortex, decreasing construct stiffness, but with no difference in fixation stability. 21 24 Since Group 1 had a hole size in the near-cortex 0.5 mm larger than the screw size, this probably was not adequate to influence the load supported by the constructs. In contrast, the hole size 1 mm larger than the screw size in Group 3 showed increased maximum load and decreased deflection compared with Group 2, thus, suggesting that Group 3 supported the highest load with less displacement.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,[19][20][21][22][23][24] The over-drilling technique promotes an increased motion between the near-cortex and screw shaft, which reduces construct stiffness by the conventional locked plate and allows for a more symmetrical axial movement, but with no increased failure under physiological load. 23,24 The speed of bone healing is even more important if one considers free-ranging animals because of the likelihood of reintegration into the wild after treatment. The maned wolf (Chrysocyon brachyurus), which is the largest South American canid, has been designated as Near Threatened by the International Union for the Conservation of Nature because of habitat loss and other threats, including roadkill, retaliation to predation and possible diseases of domestic animals.…”
Section: Introductionmentioning
confidence: 99%